If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -6 = 2cx Solving -6 = 2cx Solving for variable 'c'. Move all terms containing c to the left, all other terms to the right. Add '-2cx' to each side of the equation. -6 + -2cx = 2cx + -2cx Combine like terms: 2cx + -2cx = 0 -6 + -2cx = 0 Add '6' to each side of the equation. -6 + 6 + -2cx = 0 + 6 Combine like terms: -6 + 6 = 0 0 + -2cx = 0 + 6 -2cx = 0 + 6 Combine like terms: 0 + 6 = 6 -2cx = 6 Divide each side by '-2x'. c = -3x-1 Simplifying c = -3x-1
| 1/3x5/9=2/9 | | 1/3x5/9= | | 5x-1+5(7x+3)= | | 8(8+4r)-2(2r+2)=-52 | | 5a-4=3a+34 | | 5a-4=3a-34 | | =(3x-9)(3x-9)(3x-9)(3x-9) | | 0=7x^4-2x^2+1 | | -2p+7=-6 | | 0.40x+0.05(2-x)=0.10(22) | | f(x)=3x^2+4x-10 | | 2-(x-11)=5(x+7) | | 5x+36=96 | | -1.54=x-2.9 | | 5-3x=2(x+10) | | 2-(x-8)=5(x+11) | | 30x^2+17= | | 1+8(-2+3)=-(3z-1)-7 | | (x)=2x^3+x-5 | | log3^1/27 | | log(x-5)=4 | | ln(x-7)=-4 | | (x-7)=-4 | | -.05x+40=.10x+10 | | -16n+4=-15n-12 | | -5((5-7)-(3-11))7-(5-13)=x | | 0.3=-log(x) | | 10/2.5= | | 81x-2*9x=8*3x | | -11b-2b=13 | | 3q+2q-4q=18 | | -5(4-x)+x= |